Leadership, power and status stratification : with reference to Bushmen, Hottentot and Ovambo society - Van Tonder, Louis L.(Louis Lourens) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1963.